PPCU: Proportional per-packet consistent updates for Software Defined Networks - Sukapuram, Radhika; Barua, Gautam (ICNP : 2016 IEEE 24th International Conference on Network Protocols : 8-11 November 2016, Singapore, 2016)
Per-packet consistency (PPC) is preserved, if during an update to a Software Defined Network (SDN), every packet either matches the new rules added or the old rules to be deleted, but not a combination of both. We propose a general update algorithm called PPCU that preserves PPC, is concurrent and provides an all-or-nothing semantics for an update, irrespective of the execution speeds of switches and links, while confining changes to only the affected switches and affected rules.